Implementation IT Governance Using COBIT 5 Framework at PT. XYZ (Persero) - Drago Tinus; Johan Setiawan (Universitas Multimedia Nusantara, 2022)
PT. XYZ (Persero) is one of the state-owned companies that move in insurance & guarantee, capital market & investment. PT. XYZ (Persero) conducts an assessment of information technology governance with the aim of meeting the implementation of GCG (Good Corporate Governance) which are listed through KBUMN (Ministry of State-Owned Enterprises) regulations PER-02/MBU/2013 & PER-03/MBU/02 /2018. The regulation PER-02/MBU/2013 has been stipulated on page 6 section 3.2. The target is that “The maturity level target in the next 5 years is a minimum maturity level of 3 in accordance with the specified maturity level”.PT. XYZ will conduct a COBIT 5 assessment again based on the results of the assessment that has been carried out by the previous assessor. COBIT 5 assessment will be carried out with a target of level 4 so that it is expected to get a maturity value above 3 and can meet the request of KBUMN (Ministry of State-Owned Enterprises).The assessment is doing by identifying company objectives, mapping Enterprise Goals, mapping IT Related Goals, mapping and determining process domains, analysis the previous assessor's COBIT 5 capability level measurement, measuring the process capability level of EDM01, EDM02 and EDM04, results and gap analysis as well as improvement recommendations.Based on the assessment that has been carried out on the EDM01, EDM02 & EDM04 process, the final result is obtained with a final value of 97.08% so that it gets a Capability Level of 3,88 and it has a gap of 0,12 from the expected target.